Composites of construction waste with niobic acid as a new eco-friendly alternative for phosphate adsorption - Lucas Lacerda Cabral; Anna Vitória Cardoso Martins; Isabele Stresser Aleluia; Janete Erika Fujihara; André Nagalli; Fernando Hermes Passig; Roberta Carolina Pelissari Rizzo-Domingues; Karina Querne de Carvalho (Desalination and Water Treatment)
Phosphate is an essential nutrient, but at high concentrations, it causes eutrophication, a global environmental concern. This study presents a novel approach for phosphate removal applying composites from construction waste (autoclaved aerated concrete, AC, and red ceramic, RC) modified with niobic acid (NA). The composites were chemically (NAC and NRC) and thermochemically (NTAC and NTRC) activated, and their physicochemical and morphological properties were thoroughly characterized. NAC (1.99 m2 g−1), NTAC (0.40 m2 g−1), NRC (5.72 m2 g−1), and NTRC (0.53 m2 g−1) showed low specific surface areas, rough and porous structures and adhered NA grains. The composites exhibited high phosphate removal efficiencies - 80.6 % after 24 h for NAC and 97.5 % within 60 min for NTAC. Adsorption kinetics followed the pseudo-second-order model (0.51 mg g−1 for NAC; 0.29 mg g−1 for NTAC), suggesting chemisorption and equilibrium data fit the Sips model for NAC (R2 = 0.99 and Δqe = 0.14 %) and Langmuir model for NTAC (R2 = 0.99 and Δqe = 0.10 %), indicating heterogeneous and monolayer adsorption, respectively. The proposed mechanisms included pore-filling, electrostatic attraction, surface precipitation and complexation with niobium. These findings underscore the potential of NA-modified construction waste composites as efficient, sustainable phosphate adsorbents for wastewater treatment.